Multi-isotope zooarchaeological investigations at Abri du Maras: The paleoecological and paleoenvironmental context of Neanderthal subsistence strategies in the Rhône Valley during MIS 3. Issue 174 (January 2023) - Britton, Kate; Jimenez, Elodie-Laure; Le Corre, Mael; Pederzani, Sarah; Daujeard, Camille; Jaouen, Klervia; Vettese, Delphine; Tütken, Thomas; Hublin, Jean-Jacques; Moncel, Marie-Hélène
Abstract: The exploitation of mid- and large-sized herbivores (ungulates) was central to hominin subsistence across Late Pleistocene Europe. Reconstructing the paleoecology of prey-taxa is key to better understanding procurement strategies, decisions and behaviors, and the isotope analysis of faunal bones and teeth found at archaeological sites represent a powerful means of accessing information about past faunal behaviors. These isotope zooarchaeological approaches also have a near-unique ability to reveal environmental conditions contemporary to the human activities that produced these remains. Here, we present the results of a multi-isotope, multitissue study of ungulate remains from the Middle Paleolithic site of Abri du Maras, southern France, providing new insights into the living landscapes of the Rhône Valley during MIS 3 (level 4.2 = 55 ± 2 to 42 ± 3 ka; level 4.1 = 46 ± 3 to 40 ± 3 ka). Isotope data (carbon, nitrogen) reveal the dietary niches of different ungulate taxa, including the now-extinct giant deer ( Megaloceros ). Oxygen isotope data are consistent with a mild seasonal climate during level 4.2, where horse ( Equus ), bison ( Bison ), and red deer ( Cervus elaphus ) were exploited year-round. Strontium and sulfur isotope analyses provide new evidence for behavioral plasticity in Late Pleistocene European reindeer ( Rangifer ) between level 4.2 and level 4.1, indicating a change from the migratory to the sedentary ecotype. In level 4.1, the strong seasonal nature of reindeer exploitation, combined with their nonmigratory behavior, is consistent with a seasonally restricted use of the site by Neanderthals at that time or the preferential hunting of reindeer when in peak physical condition during the autumn.